Pengaruh budaya kaizen dan talent management terhadap kinerja karyawan dengan reward sebagai variabel moderasi pada cv. sumber beton kota lubuklinggau - Nova Eliza, Nova Eliza; Dheo Rimbano; Astri Riance (JEBIM Prima, 2025)
This study investigates the influence of Kaizen Culture and Talent Management on employee performance, with Reward as a moderating variable at CV. Sumber Beton, Lubuklinggau City. Using a quantitative approach, data were collected from 40 employee respondents. The results reveal that Kaizen Culture has a significant positive effect on employee performance, with a path coefficient of -0.519 and a p-value of 0.004. Talent Management shows a significant positive effect, with a path coefficient of 0.670 and a p-value of 0.000. However, Reward does not significantly moderate the relationship between Kaizen Culture and employee performance, as indicated by a p-value of 0.363. Similarly, Reward fails to significantly moderate the effect of Talent Management on performance, with a p-value of 0.455. These findings suggest that while Kaizen Culture and Talent Management directly affect employee performance, Reward does not strengthen these relationships and may even weaken them. This study highlights the importance of focusing on internal cultural and talent development strategies rather than relying solely on reward systems to enhance employee performance.